2017
DOI: 10.7243/2057-1631-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of biological samples from non-metastatic breast cancer patients

Abstract: Background: Breast cancer (BC) is one of the most common non-skin cancers in women and the fifth most common cause of cancer death worldwide. Both the prognosis and survival rate of BC patient improve considerably if the disease is discovered at an early stage. Methods: In the present study, we analyzed qualitatively and quantitatively volatile organic compounds (VOCs) in the headspace over urine, blood and tissue samples to identify VOCs characteristic for diagnosing BC. The study comprised 150 women with non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Different oxidizable simple or complex mixtures of organic substances having a vapour phase are detected using a 10‐fold array of thick film metal‐oxide gas sensors. Their names and sensitivity characteristics are summarized in Table 1, as we detailed earlier 10 . Stability studies on a single blood sample over 72 h showed no significant differences in E‐Nose sensor responses, allowing the blood sample to be analysed as they arrived in the laboratory or after being stored overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Different oxidizable simple or complex mixtures of organic substances having a vapour phase are detected using a 10‐fold array of thick film metal‐oxide gas sensors. Their names and sensitivity characteristics are summarized in Table 1, as we detailed earlier 10 . Stability studies on a single blood sample over 72 h showed no significant differences in E‐Nose sensor responses, allowing the blood sample to be analysed as they arrived in the laboratory or after being stored overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Their names and sensitivity characteristics are summarized in Table 1, as we detailed earlier. 10 Stability studies on a single blood sample over 72 h showed no significant differences in E-Nose sensor responses, allowing the blood sample to be analysed as they arrived in the laboratory or after being stored overnight at 4°C. were extracted and further analysed, as we detailed earlier.…”
Section: Electronic Nose (E-nose)mentioning
confidence: 98%
See 3 more Smart Citations